Dopant-Free Ultra-Thin Spiro-OMeTAD Enables Near 30%-Efficient n–i–p Perovskite/Silicon Tandem Solar Cells - Xue, Xiangying; Yang, Weichuang; Ying, Zhiqin; Cao, Fangfang; Zeng, Yuheng; Yang, Zhenhai; Yang, Xi; Ye, Jichun (Nano-Micro Letters, 2026)
A major challenge for n–i–p structured perovskite/silicon tandem solar cells (TSCs) is the use of 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (spiro-OMeTAD), a commonly used hole transport layer, which induces significant optical losses and consequently reduces device current. Herein, we propose an ultra-thin (10 nm) vacuum thermal evaporation (VTE)-deposited spiro-OMeTAD, coupled with a 2D/3D perovskite heterojunction, to simultaneously enhance the optical and electrical properties of n–i–p perovskite/silicon TSCs. Our results demonstrate that the 10-nm-thick spiro-OMeTAD layer significantly improves optical performance, achieving a 92.2% reduction in parasitic absorption and an 18.4% decrease in reflection losses. Additionally, the incorporation of the 2D/3D perovskite heterojunction facilitates improved molecular arrangement and enhanced surface uniformity of the ultrathin spiro-OMeTAD, leading to higher tolerance to interface defects and more efficient hole extraction. Consequently, n–i–p perovskite/silicon TSCs featuring ultrathin spiro-OMeTAD exhibit remarkable efficiencies of 29.73% (0.135 cm2) and 28.77% (28.25% certified efficiency, 1.012 cm2), along with improved stability. Highlights: 1 Optical loss reduction: The 10-nm-thick vacuum thermal evaporation (VTE)-based 2,2′,7,7′-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9′-spirobifluorene (spiro-OMeTAD) film reduces parasitic absorption by 92.2% and reflection losses by 18.4% compared to conventional spin-coated 200-nm-thick spiro-OMeTAD. 2 Electrical performance improvement: The VTE-deposited spiro-OMeTAD, coupled with a 2D/3D perovskite heterojunction, ensures conformal coverage, optimizes energy-level alignment, and passivates interface defects. 3 Device efficiency and stability enhancement of perovskite/silicon tandems: A remarkable efficiency of 29.73% is achieved, the highest reported value for spiro-OMeTAD-based n–i–p tandems, with a 11 times improvement of stability under operational conditions.